2019
DOI: 10.1097/coc.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Intrapatient Molecular and Histologic Heterogeneity After First-generation or Second-generation TKI Therapy of NSCLC Patients

Abstract: Objectives: The discovery of tyrosine kinase inhibitors (TKI) has remarkably improved the clinical course of patients with non–small cell lung cancer driven by Epidermal Growth Factor Receptor (EGFR) mutations. However, virtually in all cases, the disease resurfaces in a TKI-resistant form that is mainly linked to an acquired EGFR-T790M mutation, a MET amplification, or small cell lung cancer (SCLC) transformation. Third-generation TKIs are able to block tumor growth through an irreversible binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Unlike tissue-based tumor molecular analysis, liquid biopsy allows minimally invasive genomic profiling and, if performed serially, may provide a more comprehensive information regarding global tumor evolution occurring at different metastatic sites throughout the course of disease. Additionally, liquid biopsy can be a useful tool for detection of emerging resistant tumor subclones [64,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike tissue-based tumor molecular analysis, liquid biopsy allows minimally invasive genomic profiling and, if performed serially, may provide a more comprehensive information regarding global tumor evolution occurring at different metastatic sites throughout the course of disease. Additionally, liquid biopsy can be a useful tool for detection of emerging resistant tumor subclones [64,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…A 76-year-old female patient with EGFR L858R-mutant adenocarcinoma was diagnosed with SCLC transformation with consistent L858R mutation and received chemotherapy (cisplatin and etoposide) as the subsequent treatment for 5 months, after which she underwent both chemotherapy and immunotherapy (amrubicin, nivolumab, and irinotecan); however, further progression was observed after 6 months, and a second re-biopsy revealed both L858R and T790M mutations, which led to the administration of osimertinib, and a partial response was achieved and lasted for 3 months [ 45 ]. In addition, some of the SCLC-transformed patients experienced further gene mutations and histologic changes, and it was reported that NSCLC could be dominant again during treatment [ 46 , 47 , 48 , 49 ]. Therefore, treatment strategies should be selected according to the individual characteristics of patients.…”
Section: Enhanced Awareness and Individualized Treatmentmentioning
confidence: 99%